2022
DOI: 10.3389/fcell.2022.853003
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear GSK-3β and Oncogenic KRas Lead to the Retention of Pancreatic Ductal Progenitor Cells Phenotypically Similar to Those Seen in IPMN

Abstract: Glycogen synthase kinase-3β (GSK-3β) is a downstream target of oncogenic KRas and can accumulate in the nucleus in pancreatic ductal adenocarcinoma (PDA). To determine the interplay between oncogenic KRas and nuclear GSK-3β in PDA development, we generated Lox-STOP-Lox (LSL) nuclear-targeted GSK-3β animals and crossed them with LSL-KRasG12D mice under the control of the Pdx1-cre transgene—referred to as KNGC. Interestingly, 4-week-old KNGC animals show a profound loss of acinar cells, the expansion of ductal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…Tff2), it can also be an initial step towards dysplasia and tumorigenesis [9, 10]. Interestingly, analogous gastric pit and SPEM markers are also characteristic of low grade (gastric) IPMNs, which are the most common subtype of IPMNs [23, 24, 25]. Our findings demonstrate that mutant GNAS at least partially contributes to the gastric metaplastic phenotype characteristic of low-grade IPMNs.…”
Section: Discussionmentioning
confidence: 59%
“…Tff2), it can also be an initial step towards dysplasia and tumorigenesis [9, 10]. Interestingly, analogous gastric pit and SPEM markers are also characteristic of low grade (gastric) IPMNs, which are the most common subtype of IPMNs [23, 24, 25]. Our findings demonstrate that mutant GNAS at least partially contributes to the gastric metaplastic phenotype characteristic of low-grade IPMNs.…”
Section: Discussionmentioning
confidence: 59%
“…We are hard pressed to understand what drives cyst formation in these cases, though our data suggest that KRAS is sufficient and that these IPMN may be MUCL3-negative. Studies in mice have suggested the formation of IPMN-like, AQP5+ lesions driven be oncogenic KRAS and nuclear expression of GSK3β 51 . Further, a recent study shows that loss of RNF43 expression in the context of oncogenic KRAS expression is sufficient to drive IPMN/cyst formation and accelerated tumorigenesis in mice 52 .…”
Section: Discussionmentioning
confidence: 99%
“…lesions driven be oncogenic KRAS and nuclear expression of GSK3b 51 . Further, a recent study shows that loss of RNF43 expression in the context of oncogenic KRAS expression is sufficient to drive IPMN/cyst formation and accelerated tumorigenesis in mice 52 .…”
Section: Discussionmentioning
confidence: 99%
“…In IPMNs with high-grade dysplasia, a relative depletion of T-cells with enriched macrophages is present compared to low-grade dysplasia [ 73 , 74 ]. Glycogen synthase kinase-3beta (GSK-3β) and KRASG12D promote the retention of pancreatic ductal progenitor cells and are new lineage biomarkers related to IPMN and pancreatic cancer [ 75 ]. In current clinical practice, none of the known biomarkers allow for the selection of candidates for surgery, observation, or neither [ 76 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…Glycogen synthase kinase-3beta (GSK-3β) and KRAS G12D promote the retention of pancreatic ductal progenitor cells and are new lineage biomarkers related to IPMN and pancreatic cancer [75].…”
Section:  Diagnosismentioning
confidence: 99%